Chemoselective acylation of 2-amino-8-quinolinol in the generation of C2-amides or C8-esters. Issue 67 (30th August 2017) - Park, Yongseok; Fei, Xiang; Yuan, Yue; Lee, Sanha; Hur, Joonseong; Park, Sung Jean; Jung, Jae-Kyung; Seo, Seung-Yong
Abstract : Chemoselective controls in acylation of 2-amino-8-quinolinol. Abstract : Two different ways to carry out the chemoselective acylation of 2-amino-8-quinolinol with unique features to generate C2-amides or C8-esters were developed. The coupling reaction with a variety of carboxylic acids using EDCI and DMAP provided C8-ester derivatives, whereas N -heteroaromatic acids were not introduced on the C8-hydroxy group, but rather on the C2-amino group under the same conditions. To obtain C2-amides selectively, the anionic nucleophile from 2-amino-8-quinolinol was treated with less reactive acyl imidazolides or esters.